Bile acid receptors regulate the role of intestinal macrophages in inflammatory bowel disease - Yang, Hongjie; Shi, Xianhong; Wang, Beibei; Li, Heng; Li, Bin; Zhou, Tianqi; Tian, Lulu; Wang, Shengjun; Yin, Kai (Frontiers in Immunology, 2025)
Many factors, including genetic vulnerability, barrier function, intestinal immune cells, and intestinal microbiota, may combine to affect the occurrence and progression of inflammatory bowel disease (IBD). Through targeting bile acid receptors (BARs), bile acids have been demonstrated to have a range of regulatory effects on intestinal immune responses in recent decades. As the basis of intestinal immunity, macrophages play an indispensable role in intestinal homeostasis. BARs connect the intestinal microbiota with immune cells, significantly impacting IBD. This review focuses on the role of bile acids in regulating the differentiation and function of intestinal macrophages in IBD.